Quality Evaluation of Iranian Honey Collected from Khorasan Province, Iran - Asma Afshari; Mahdi Ram; Sara Mohamadi (International Journal of Food Science)
Honey is a prominent nutritional and medicinal production of honey bees, originating from the nectar of flowers. The physicochemical properties of honey serve as indicators of its freshness and originality. The current survey aimed to assess the parameters of quality control, including hydroxymethylfurfuraldehyde [HMF], reducing sugars, fructose/glucose, sucrose, proline content, distaste activity, and free acidity, in 25 honey samples of different brands available in Khorasan Province, Iran. We used the methods suggested by the Association of Official Analytical Collaboration (AOAC, 1995), the International Honey Commission (IHC, 2009), and the Codex Alimentarius Honey Standards for the study. Statistical analysis was performed in Microsoft Excel. The obtained data indicated that eight out of 25 analyzed samples (32%) complied with all the requirements and were generally of acceptable quality. Meanwhile, 17 samples (68%) were unconfirmed by the Iranian Standard Organization (ISO), including 12 samples with a low level of diastase (<8 Schade) and high levels of HMF (>15 mg/kg), two samples with high sucrose levels, two samples with high proline, and one sample with high HMF. These findings suggested their inappropriate storage (time/temperature), heat treatment, and/or adulteration with industrial sugar. According to the results, the examined honey samples produced in Khorasan Province were not of acceptable quality, which highlights the importance of an effective regulatory framework to be evaluated and rectified periodically and accurately to maintain consumer rights, as well as public health.